Load Frequency Control of DFIG-isolated and Grid Connected Mode - Krishnan Manickavasagam (Institute of Advanced Engineering and Science, 2012)
Wind energy is one of the extraordinary promising sources of renewable energy due to its clean character, free availability and economic viability. A Doubly Fed Induction Generator (DFIG) feeds power from both the stator and the rotor windings at speeds above synchronous speed of the machine. This paper deals the load frequency control of doubly fed induction generator in isolated mode and grid connected mode. The wind turbine model is obtained using MATLAB/ SIMULINK which consists of DFIG, rotor side rectifier, grid side inverter and grid. This model is controlled by conventional controllerand proposed Load Frequency Control (LFC) method. The results are proven that frequency control gives better results in all the aspects